Modelación digital de dispersión sonora con parámetros de acuerdo a la normativa legal vigente, a partir de datos de muestreo de ruido, en la parroquia La Matriz cantón Latacunga provincia de Cotopaxi, 2020. - Robalino Santillán, Darwin Bladimir (2020)
The damage caused by environmental noise to the population is undetectable; therefore, it is necessary to carry out constant noise monitoring by the competent authority. For the analysis, interpretation, decision making, and the determination of the areas affected by noise, a digital acoustic/sound dispersion model has been developed where the influenced areas of noise pollution can be appreciated in the best way; it also allows visualizing the ranges of contamination that each area has. The data used for designing the digital acoustic/sound dispersion model were obtained from different noise studies carried out in Latacunga city. Geographic information systems and office packages for data classification were used in the design of the map. To obtain the base map, DEM files were used, obtained from the ALOS PALSAR satellite's ASF website. The base map enables the interpolation of data; therefore, the digital acoustic/sound dispersion model's generation was possible. Finally, the acoustic map allows to analyze the amount of affectation that exists in each area where six ranges were assigned at different levels; each one represented an area with specific groups of data in which the following results were obtained: the ranges 1 to 4 show that 80% of the zones are within the maximum permissible limits complying with the regulations established in Ecuador, while ranges 5 and 6 represent only 60% and 20% of compliance with regulations. The zone that is not within the maximum permissible limits, which is the most affected, is the hospital and educational zone exceeding 45 to 35dB.